Multi‐scale habitat selection of Mus minutoides in the Lowveld of Swaziland. (28th December 2012) - Long, Andrea K.; Bailey, Karen; Greene, Daniel U.; Tye, Courtney; Parr, Courtnee; Lepage, Heather K.; Gielow, Kurt H.; Monadjem, Ara; McCleery, Robert A.
Abstract: We investigated habitat selection of Mus minutoides in northeastern Swaziland. We used powder tracking to determine how M. minutoides selected habitat at a fine scale and a broader path scale. At the fine scale, we measured per cent cover of grass and shrubs, the number of forbs and visual obstruction (VO) at five evenly spaced points along a mouse's pathway and at a paired random location. At the path scale, we calculated the relative displacement (RD) of each path as the ratio of the distance from the start to the end point of the path to the total length of the path (values near one indicate less preference). We found that M. minutoides were positively associated with increases in visual obstruction, grass cover, and shrub cover at the fine scale, but not at the path scale. Our results indicate that M. minutoides selection of vegetative features at the path scale is not as important as their fine‐scale selection of vegetative structure. In addition, the shrub encroachment on our study site may be directly beneficial to M. minutoides at the fine scale. Our results provide us with an increased understanding of the basic ecology of M. minutoides and information on their response to a changing landscape.